河北省农业强省建设分析及对策研究 = The advantage analysis of Hebei's agriculture and development strategy - 李凤强 Li, Fengqiang (2008)
A linear regressive model of developing a strong agricultural economy was established. The author used this model to analyze the agricultural economy in Hebei.